Evaluasi Pengukuran Usability Menggunakan Metode Heuristic Evaluation Pada Aplikasi Duolingo Berbasis Android - dicky azhary octavianto, muhammad; Muhammad Dicky Azhary Octavianto; Tata Subtari (Jurnal Manajemen Informatika & Teknologi, 2025)
The development of digital technology has brought significant changes in the field of education, including in foreign language learning. One of the widely used mobile learning platforms is Duolingo, an Android-based application. This study aims to start the usability of the Duolingo application using the Heuristic Evaluation method, based on the ten heuristic principles of Nielsen. This type of research is descriptive with an evaluative approach, involving three evaluators who independently assess the user interface. The evaluation results show that Duolingo has a fairly good level of usability, especially in terms of navigation, minimalist design, and system visibility. However, several usability issues were identified in the control of user principles and freedom, help and documentation, and error prevention. The average severity of the identified problems ranged from mild to moderate, with no critical issues found. Based on these findings, this study provides recommendations for improvements so that the application can offer a more optimal learning experience. The results of the study are expected to be valuable input for developers in improving the quality of Duolingo's usability as a mobile-based language learning tool.